Vocational Training for Rural Workers in the Context of Economic Restructuring in Ha Tinh Province, Vietnam - Tho, Bui Thi Quynh; Nhung, Nguyen Thi Kim; Ngoc , Tran Hai; Khanh, Tran Thi (Asian Journal of Agriculture and Rural Development, 2020)
Labor force development is one of the strategic solutions in the process of shifting the agricultural and rural economy to commodity production in accordance with economic restructuring. The article aims at discussing the trend of economic restructuring in Ha Tinh province in recent years, surveying vocational training needs of rural workers and vocational training results in Ha Tinh province in the context of economic restructuring. The research utilizes a binary logit model for primary data collected in a sample of 334 working-age people in Ha Tinh province to examine the vocational training needs of rural laborers in Ha Tinh. It is found that economic restructuring and state policies have a significant effect on the vocational training needs of rural workers. In addition, the change in vocational training pattern is relatively in line with the change in economic restructuring. The study also gives some recommendations for rural vocational training policy in Ha Tinh province.